Family Support Serves as Key determinants Influencing the Utilization of the Integrated Health Service Post for the Elderly - Anggun Pratiwi; Husna Yetti; Rosfita Rasyid (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Utilization of the Posyandu Lansia remains suboptimal in the Belimbing Health Center despite its essential role in preventive health services for older adults. Various demographic and behavioral factors have been examined, yet the determinants influencing service utilization remain inconsistent across studies. This study aimed to identify the factors associated with the utilization of the Posyandu Lansia, with a particular focus on the role of family support as a potential determinant. A quantitative analytic study with a cross sectional design was conducted among older adults registered in the Belimbing Health Center. Data were collected using a validated questionnaire measuring demographic characteristics, knowledge, attitudes, family support, health worker support, and accessibility. Statistical analysis included descriptive and bivariate testing using the Chi square method. The findings revealed that family support was the only factor significantly associated with the utilization of the Posyandu Lansia. Emotional encouragement was generally adequate, yet gaps were evident in instrumental support such as transportation and physical accompaniment, as well as informational support such as schedule reminders. Other variables including age, sex, education, occupation, knowledge, attitude, distance, and health worker support showed no significant association with service utilization. In conclusion, family support serves as the primary determinant of Posyandu Lansia utilization. Strengthening instrumental and informational support within the household is essential to improving attendance and ensuring consistent engagement in preventive health services among older adults.Keywords: Posyandu Lansia; service utilization; family support